2008
DOI: 10.1515/znc-2008-11-1214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigations of the Soil, Rhizosphere and Transgenic Glufosinate-Resistant Rape and Maize Plants in Combination with Herbicide (Basta®) Application under Field Conditions

Abstract: A field study was conducted during 1994 to 1998 on the Experimental Farm Roggenstein, near Fürstenfeldbruck, Bavaria, Germany to determine the effect of transgenic glufosinateresistant rape in combination with the herbicide Basta " [glufosinate-ammonium, phosphinothricin, ammonium (2RS)-2-amino-4-(methylphosphinato) butyric acid] application on soil microorganisms and the behaviour of the synthetic transgenic DNA in response to normal agricultural practice. No influence of Basta " on microbial biomass could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Information concerning the effects of glufosinate on microbial community composition is limited. As seen in our study, recommended doses of glufosinate in the form of Basta and Liberty have been shown to have negligible effects on microbial community composition as represented by PLFA 18 and DNA fingerprinting 19 , respectively. For paraquat and paraquat-diquat, information concerning their effects on soil microbial community composition is even more limited.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Information concerning the effects of glufosinate on microbial community composition is limited. As seen in our study, recommended doses of glufosinate in the form of Basta and Liberty have been shown to have negligible effects on microbial community composition as represented by PLFA 18 and DNA fingerprinting 19 , respectively. For paraquat and paraquat-diquat, information concerning their effects on soil microbial community composition is even more limited.…”
Section: Resultssupporting
confidence: 57%
“…For glufosinate, which is a chemical relative of glyphosate, some studies indicate that low-levels (≤10 mg/kg) exert significant positive and negative effects on the relative abundances of various bacterial taxa when applied as Basta 15 , 16 and Liberty 17 , while others demonstrate that similar application rates of Basta 18 and Liberty 19 have no effect on microbial community structure.…”
Section: Introductionmentioning
confidence: 99%
“…E.g. Ernst et al (2008) detected no influence of Basta ® herbicide at a dose of 600 g per ha on soil microbial biomass in the field experiments. On the other hand, Griffiths et al (2008) in glasshouse experiment using the same herbicide dose as Ernst et al (2008) observed that glufosinate application in general altered the community level physiological profile of the microbial community and reduced both the soil basal respiration and the abundance of protozoa but, compared to other standard agricultural practices, the differences were relatively small.…”
Section: Resultsmentioning
confidence: 79%
“…However, Schmalenberger and Tebbe (2003) did not detect changes in the bacterial community structure after glufosinate application to conventional or transgenic herbicide-tolerant maize, using molecular methods. Likewise, Ernst et al (2008) found no impact on bacterial community structure when glufosinate (0.6 kg ha -1 ) was applied to glufosinate-resistant rape/maize. The contradictory nature of these results may be a consequence of different monitoring periods and environmental conditions, as Griffiths et al (2008) found altered microbial diversity (CLPP and ester-linked FAME) at 6 weeks after herbicide application but no differences at 12 weeks.…”
Section: [Insert Table 4 Near Here]mentioning
confidence: 88%
“…Nevertheless, the actual community structure had shifted at 60 d from controls in all acetochlor treatments (Xin-Yu et al, 2010). Applications of metazachlor (0.5 kg ha -1 ) also altered the PLFA community structure in the rhizosphere of non-transgenic canola (Ernst et al, 2008), but measurements were made at one unspecified time, so no assessment of resilience could be made. Pretilachlor (0.45 kg ha -1 ) had no significant impact on MBC or PLFA profiles in a rice paddy soil (Murata et al, 2004).…”
Section: Chloroacetanilidesmentioning
confidence: 99%